Elemen Arsitektural Astana Sunda Kasepuhan Ciptagelar - Noeviyanti Indah Laksana; Lisa Dwi Wulandari; Susilo Kusdiwanggo (RUAS, 2021)
Kasepuhan Ciptagelar is a kasepuhan who still holds the ngalalakon tradition. Based on the traces of the movement, the artifacts left are not only settlements or houses but also artifacts that are outside the settlements in the form of astana (tomb). Physically, this astana has differences from other tombs because the astana adapts to environmental conditions. This study aims to identify the architectural elements of Astana Sunda Kasepuhan Ciptagelar, to determine its characteristics. The research method is a qualitative research with descriptive analysis. The results show that the architectural elements of Astana Sunda Kasepuhan Ciptagelar are influenced by Sundanese culture, nature and the environment, with the main character is the use of natural materials around the. The basic form of plan is rectangle, with or without pangkemit. All astana have woven bamboo walls, rectangle windows and doors in several variants, roof in the form of parahu kumureb and Suhunan Jolopon. The original roof are made of palm-fibers, and the ceiling under the roof are using woven bamboo.